2020
DOI: 10.1017/s1431927620000161
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Molecular, and Pathological Appraisal ofHymenolepis nana(Hymenolepididae) Infecting Laboratory Mice (Mus musculus)

Abstract: Hymenolepis nana, typically a parasite found in conventionally established mouse colonies, has zoonotic potential characterized by autoinfection and direct life cycle. The objective of this study was to determine the rate of parasite infection in laboratory mice. The hymenolepidide cestode infected 40% of the 50 mice sampled. The rate of infection in males (52%) was higher than in females (28%). Morphological studies on the cestode parasite showed that worms had a globular scolex with four suckers, a retractab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
1
0
Order By: Relevance
“…In the present study, the intestinal tissue showed abnormal architecture after the infection with H. nana, which agreed with the previous report by Mohammed and Sulaiman (2014) and Al-Olayan et al (2020) reported severe damage for the intestinal tissue upon infection. Moreover, treatment with AF and AF-NPs against H. nana has eliminated the infection while protecting the jejunum from parasite-induced injury, whereas the intestinal tissue of post-treated mice with PZQ revealed an improvement in the tissue except for the presence of ulcers this presents similar findings to Chiamah et al (2019).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, the intestinal tissue showed abnormal architecture after the infection with H. nana, which agreed with the previous report by Mohammed and Sulaiman (2014) and Al-Olayan et al (2020) reported severe damage for the intestinal tissue upon infection. Moreover, treatment with AF and AF-NPs against H. nana has eliminated the infection while protecting the jejunum from parasite-induced injury, whereas the intestinal tissue of post-treated mice with PZQ revealed an improvement in the tissue except for the presence of ulcers this presents similar findings to Chiamah et al (2019).…”
Section: Discussionsupporting
confidence: 94%
“…It is known to infect both human beings and rodents (Shirvan et al, 2016). The infection occurs directly from the ingestion of contaminated food and water with H. nana eggs (Al-Olayan et al, 2020). Infections might cause a variety of symptoms such as irritability, abdominal pain, loss of appetite, diarrhea and even dizziness (Lin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…M < F Mus musculus [151] Ascaris spp. M > F Homo sapiens [150] Hymenolepis nana M > F Mus musculus, Homo sapiens [152,153] Toxocara spp. NDCanis lupus familiaris, Canis lupus, Vulpes [154] Ancylostoma spp.…”
Section: Nematodes Cestodes Trematodesmentioning
confidence: 99%
“…The second one is also known as the rat tapeworm and the adults measure 20 to 60 cm in length (Fig. 1,2) (Al-Olayan et al 2020). The scolex of H. nana bears a retractable rostellum, armed with a single circle of 20 to 30 hooks (Fig.…”
Section: Etiological Agentsmentioning
confidence: 99%